Accidents in Childhood: A Report on 17,141 Accidents - Keddy, J. Arthur (1964)
The causes of injury to 17,141 children brought to the emergency department of a large pediatric hospital in one year were studied. The leading causes of injury were: falls, 5682; cuts or piercings, 1902; poisonings, 1597; and transportation accidents, 1368. Included in these are 587 falls on or down stairs, 401 cuts due to glass, 630 poisonings from household or workshop substances, 510 poisonings from salicylate tablets, and 449 accidents involving bicycles or tricycles. Other findings included 333 injuries to fingers or hands in doors, usually car doors; 122 instances of pulled arms; 384 ingestions and 53 inhalations of foreign bodies; 60 alleged sexual assaults, 58 chemical burns, 127 wringer injuries, and four attempted suicides. A rewarding opportunity in accident prevention exists for hospitals that undertake to compile and distribute pertinent source data.